Use of mental health support apps in times of the COVID-19 pandemic (Research, Society and Development, 2022)
Based on the above, a critical-reflective review of the scientific literature was carried out on the use of mental health support applications in times of the COVID-19 pandemic. It’s about a narrative review, based on broad publications, appropriate to describe and discuss the development of a given subject, from a theoretical or conceptual point of view. The search was carried out by surveying the productions related to the subject of mental health support applications in times of the COVID-19 pandemic, in the Medline and PubMed databases, by crossing descriptors and applying the inclusion and exclusion criteria. In addition, the review also looked for applications that appeared on the Google Play digital platform. From the analyses, filtering and reading, ten applications were identified, of which two were found in databases and eight in virtual platforms. The applications found in the databases are related to technology-client interaction, seeking to strengthen the communication link and provide information to improve the physical and mental health of users. As for those found on the digital platform, all were aimed at promoting mental health, using monitoring and self-care tools regarding mental disorders. Among the applications studied, it was dazzled that the use of the mobile application, in a brief and focused way, mainly for health and relationship promotion purposes, is effective to improve the well-being and the search for help for mental health of the public in general.